Time course of hemispheric cerebral volume after decompressive craniectomy in malignant middle cerebral artery stroke - Rodrigues, Thiago Pereira; Rodrigues, Mariana Athaniel Silva; Bocca, Leonardo Favi; Neto, Feres Eduardo Chaddad; Cavalheiro, Sergio; Júnior, Edson Amaro; Silva, Gisele Sampaio; Suriano, Italo Capraro; Centeno, Ricardo Silva (Arquivos de Neuro-Psiquiatria, 2023)
Background Brain edema is the leading cause of death in patients with malignant middle cerebral artery (MCA) infarction. Midline shift (MLS) has been used as a monohemispheric brain edema marker in several studies; however, it does not precisely measure brain edema. It is now possible to directly measure hemisphere brain volume. Knowledge about the time course of brain edema after malignant middle cerebral artery infarction may contribute to the condition's management.Objective Therefore, our goal was to evaluate the course of brain edema in patients with malignant MCA infarction treated with decompressive craniectomy (DC) using hemispheric volumetric measurements.Methods Patients were selected consecutively from a single tertiary hospital between 2013 and 2019. All patients were diagnosed with malignant middle cerebral artery infarction and underwent a decompressive craniectomy (DC) to treat the ischemic event. All computed tomography (CT) exams performed during the clinical care of these patients were analyzed, and the whole ischemic hemisphere volume was calculated for each CT scan.Results We analyzed 43 patients (197 CT exams). Patients' mean age at DC was 51.72 [range: 42–68] years. The mean time between the ischemic ictus and DC was 41.88 (range: 6–77) hours. The mean time between the ischemic event and the peak of hemisphere volume was 168.84 (95% confidence interval [142.08, 195.59]) hours.Conclusion In conclusion, the peak of cerebral edema in malignant MCA infarction after DC occurred on the 7th day (168.84 h) after stroke symptoms onset. Further studies evaluating therapies for brain edema even after DC should be investigated.
Keywords: Decompressive Craniectomy; Infarction, Middle Cerebral Artery; Intracranial Pressure